One flew over the cuckoo's nest - Forman, Milos; Kesey, Kent.; Fantasy Films (Berkeley, Calif. Fantasy Films, 1975)
The story of a man whose rebelliousness pits him against the head nurse of a mental ward and the full spectrum of institutional repression.
Based on the novel by Ken Kesey.
The play version of "One flew over the cuckoo's nest" is by Dale Wasserman.
VHS.
Screenplay by Lawrence Hauben and Bo Goldman ; produced by Saul Saentz and Michael Douglas ; directed by Milos Forman.
Jack Nicholson, Louise Fletcher, William Redfield, Dany DeVito, Christopher Lloyd.
Keywords: Psychiatric hospitals -- Drama; Psychiatric hospital patients -- Drama; Psychiatric nurses -- Drama; Mentally ill -- Drama; Classic comedy; Feature films